Young and elderly oral squamous cell carcinoma patients present similar angiogenic profile and predominance of M2 macrophages: Comparative immunohistochemical study. Issue 12 (9th September 2019) - Teixeira, Lucas R.; Almeida, Luciana Y.; Silva, Rodrigo N.; Mesquita, Ana T. M.; Colturato, Carla B. N.; Silveira, Heitor A.; Duarte, Andressa; Ribeiro‐Silva, Alfredo; León, Jorge E.
Abstract: Background: M2 macrophages are often detected in oral squamous cell carcinoma (OSCC), which, influenced by hypoxic conditions, appear to have high angiogenesis‐inducing capacity. However, the effects of immunosenescence on tumor‐associated macrophages (TAMs) and angiogenesis in OSCC are unknown. Methods: Fifty‐seven OSCCs were divided into 3 groups (I: <40 years [n = 17]; II: 40‐65 years [n = 20]; III: >65 years [n = 20]). Immunohistochemistry for CD68 and CD163 (TAMs), and CD34 and D2‐40 for microvessel density (MVD), microvessel area (MVA), and total vascular area (TVA) were performed. Results: All groups showed similar clinicopathological and immunohistochemical findings. Similar CD68 and CD163 expression, confirmed a M2 phenotype. MVD, MVA, and TVA were similar, however, with significant predominance of blood vessels. No significant correlation between macrophage and angiogenic markers was observed. Conclusions: A similar TAM and angiogenesis profile suggests the participation of other mechanisms, instead immunosenescence, in young and elderly OSCC patients.